FORMULASI ORGANISASI DALAM PERSPEKTIF AL-QUR'AN DAN AL-HADITS - Ghufron Jayadi (LP2M Universitas Ibrahimy, 2017)
Term organization has two general sense. First organization is defined as an institution or a functional group and Â Second is organization itself Â defined as a collection of people with a system of cooperation to achieve common goals. There are two auxiliary words contained in Qur'an to learn about this organization. The word is Shaff and the ummah. To said Shaff inspire to concept that organization must have a member that consists of a collection of people, are in a container, there is regularity, has a goal, also had leaders, occurred delegation of authority and responsibility and no intention of carrying out the task with sincerity and fighting in the street God. In order to realize a good organization, effectively, efficiently and in accordance with the needs, selectively must be based on principles of organization are grounded in the teachings of Islam.